Rat spleen leucocyte (RSL) radioimmunoassay for the detection and quantification of soluble immune complexes - Al-Khateeb, S. F. (1978)
A simple and sensitive method for the detection and quantification of soluble immune complexes in sera has been developed, by utilizing Fc receptors on rat spleen leucocyte (RSL). Aggregated human IgG (AHG) was used as an in vitro model of immune complexes and its uptake by RSL was quantified using (125)I-anti-human IgG. RSL were found to bind AHG in medium as well as in ethylenediamine tetra-acetic acid (EDTA) inactivated and absorbed serum. The limit of detection of this method was 2 μg AHG/ml in medium and 4 μg AHG/ml in serum. Sera samples from patients with thyroid disorders and from diabetics were incubated with RSL and the cells incubated with (125)I-anti-human IgG. The amount of label bound to the cells was determined and referred to a standard curve of radiolabelled antibody uptake by cells previously incubated with varying amounts of AHG in serum. The results obtained were compared with those obtained using the Raji-cell radioimmunoassay. Human anti-rat erythrocyte antibody was detected in normal human serum. The amount of complexes formed in serum by heat treatment was quantified by this method.